2019
DOI: 10.1002/ar.24224
|View full text |Cite
|
Sign up to set email alerts
|

Microanatomical Record of Cortical Bone Remodeling and High Vascularity in a Fossil Giant Rat Midshaft Femur

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 71 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…These inferences of extinct taxa rely on our understanding of the histology of extant species (e.g., Köhler et al, 2012), which has shown that key life history traits like birth, growth rate, age at maturity, and age at death are recorded in the bone microstructure (Amprino, 1947; Chinsamy et al, 1995; de Margerie et al, 2002; Castanet et al, 2004; Chinsamy and Valenzuela, 2008; Erismis and Chinsamy, 2010; Marín-Moratalla et al, 2013; Kolb et al, 2015b; Jordana et al, 2016; Nacarino-Meneses et al, 2016a; Montoya-Sanhueza and Chinsamy, 2017; Nacarino-Meneses and Köhler, 2018). In extinct mammals, palaeohistological investigations have focussed on bones of extinct rodents (Geiger et al, 2013; Kolb et al, 2015b; Orlandi-Oliveras et al, 2016; Garrone et al, 2019; Miszkiewicz et al, 2019, 2020), lagomorphs (Kolb et al, 2015b; Moncunill-Solé et al, 2016), hedgehogs (Kolb et al, 2015b), wombats (Walker et al, 2020), hippos (Kolb et al, 2015b), seals (Woolley et al, 2019), bovids (Köhler and Moyà-Solà, 2009; Marín-Moratalla et al, 2011), cervids (Amson et al, 2015; Kolb et al, 2015a; Lyras et al, 2016, 2019), ursids (Veitschegger et al, 2018), and equids (Sander and Andrássy, 2006; Martínez-Maza et al, 2014; Orlandi-Oliveras et al, 2018; Nacarino-Meneses and Orlandi-Oliveras, 2019; Zedda et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These inferences of extinct taxa rely on our understanding of the histology of extant species (e.g., Köhler et al, 2012), which has shown that key life history traits like birth, growth rate, age at maturity, and age at death are recorded in the bone microstructure (Amprino, 1947; Chinsamy et al, 1995; de Margerie et al, 2002; Castanet et al, 2004; Chinsamy and Valenzuela, 2008; Erismis and Chinsamy, 2010; Marín-Moratalla et al, 2013; Kolb et al, 2015b; Jordana et al, 2016; Nacarino-Meneses et al, 2016a; Montoya-Sanhueza and Chinsamy, 2017; Nacarino-Meneses and Köhler, 2018). In extinct mammals, palaeohistological investigations have focussed on bones of extinct rodents (Geiger et al, 2013; Kolb et al, 2015b; Orlandi-Oliveras et al, 2016; Garrone et al, 2019; Miszkiewicz et al, 2019, 2020), lagomorphs (Kolb et al, 2015b; Moncunill-Solé et al, 2016), hedgehogs (Kolb et al, 2015b), wombats (Walker et al, 2020), hippos (Kolb et al, 2015b), seals (Woolley et al, 2019), bovids (Köhler and Moyà-Solà, 2009; Marín-Moratalla et al, 2011), cervids (Amson et al, 2015; Kolb et al, 2015a; Lyras et al, 2016, 2019), ursids (Veitschegger et al, 2018), and equids (Sander and Andrássy, 2006; Martínez-Maza et al, 2014; Orlandi-Oliveras et al, 2018; Nacarino-Meneses and Orlandi-Oliveras, 2019; Zedda et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We then followed standard methods for the preparation of fossil material for histological thin sectioning (e.g. Mahoney et al, 2017;Miszkiewicz et al, 2019Miszkiewicz et al, , 2020Walker et al, 2020). The tooth was embedded in an epoxy resin solution and left to set overnight in 25 mm Buehler SamplKups ® that had been coated with a release agent.…”
Section: Methodsmentioning
confidence: 99%
“…Martiniaková et al (2005Martiniaková et al ( , 2006 found no secondary osteons in rats, aged 4-6 months. The only conclusive evidence for Haversian remodeling in a rat outside of that which was experimentally induced, comes from the femur of a fossil giant rat (Miszkiewicz et al, 2019), which displayed numerous secondary osteons. The authors claimed that the giant femur is indicative of a body size and skeletal frame "well above" that of common rats.…”
Section: Introductionmentioning
confidence: 99%